2009
DOI: 10.1016/j.neuron.2008.12.020
|View full text |Cite
|
Sign up to set email alerts
|

The Excitatory Neuronal Network of the C2 Barrel Column in Mouse Primary Somatosensory Cortex

Abstract: Local microcircuits within neocortical columns form key determinants of sensory processing. Here, we investigate the excitatory synaptic neuronal network of an anatomically defined cortical column, the C2 barrel column of mouse primary somatosensory cortex. This cortical column is known to process tactile information related to the C2 whisker. Through multiple simultaneous whole-cell recordings, we quantify connectivity maps between individual excitatory neurons located across all cortical layers of the C2 bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

139
1,089
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 839 publications
(1,266 citation statements)
references
References 81 publications
(103 reference statements)
139
1,089
5
2
Order By: Relevance
“…However, Song et al (2005) reported that the probability of connection does not depend systematically on the distance in the same neuronal type in the visual cortex. In support of the latter, Lefort et al (2009) found no significant drop in connectivity over the distances explored in a single mouse barrel. As a result, there is not sufficient evidence to suggest a significant decrease in connection probability with distance within the same barrel and, consequently, we have not incorporated such dependence in our model.…”
Section: Connection Probabilities and Delaysmentioning
confidence: 62%
See 4 more Smart Citations
“…However, Song et al (2005) reported that the probability of connection does not depend systematically on the distance in the same neuronal type in the visual cortex. In support of the latter, Lefort et al (2009) found no significant drop in connectivity over the distances explored in a single mouse barrel. As a result, there is not sufficient evidence to suggest a significant decrease in connection probability with distance within the same barrel and, consequently, we have not incorporated such dependence in our model.…”
Section: Connection Probabilities and Delaysmentioning
confidence: 62%
“…Our (Lefort et al 2009)). The proportion of excitatory to inhibitory neurons in layers II/III is approximately 9:1.…”
Section: Model Of Layers II Iii and Iv Of A Barrel Cortical Columnmentioning
confidence: 95%
See 3 more Smart Citations